Odpowiedzi

2010-04-17T21:21:44+02:00
A) (x - y)² + (x + y - 1)² = 0
(x + y - 1)² = ((x + y) - 1)² = (x + y)² - 2(x + y) + 1 =
x² + 2xy + y² - 2x - 2y + 1 = 0

x² - 2xy + y² + x² + 2xy + y² - 2x - 2y + 1 = 0
2x² + 2y² - 2x - 2y + 1= 0
2(x² - x) - 2(y - y²) + 1 = 0

b) 2x² + 2x - 2xy + y² + 1 = 0
2(x² + x) + y(y -2x) + 1 = 0
2010-04-17T21:22:11+02:00
A) (x - y)² + (x + y - 1)² = 0

(x + y - 1)² = ((x + y) - 1)² = (x + y)² - 2(x + y) + 1 =0

x² + 2xy + y² - 2x - 2y + 1 = 0

x² - 2xy + y² + x² + 2xy + y² - 2x - 2y + 1 = 0

2x² + 2y² - 2x - 2y + 1= 0

2(x² - x) - 2(y - y²) + 1 = 0



b) 2x² + 2x - 2xy + y² + 1 = 0

2(x² + x) + y(y -2x) + 1 = 0
2010-04-17T21:27:03+02:00
X²-2xy+y²+x²+y²-1=0
2x²-2xy+2y²-1=0

2)

(x-y)²+(x+1)²=0